Awareness of 'sound' in nursing homes: A large-scale soundscape survey in Flanders (Belgium). Issue 1 (March 2018) - Aletta, Francesco; Vander Mynsbrugge, Tara; Van de Velde, Dominique; De Vriendt, Patricia; Thomas, Pieter; Filipan, Karlo; Botteldooren, Dick; Devos, Paul
There are relatively few studies on the acoustic environment of care facilities. However, sound is an important component of the users' experience and quality of life in these spaces, and particularly in nursing homes, where both staff and residents have medium- to long-term perspectives, contrarily to hospital settings. This study included an online large-scale survey for nursing homes in Flanders and it targeted the group of professionals. It aimed at providing an overview about noise sensitivity and sound perception of the staff members in their work environment, as well as investigating the potential effects on sound perception of staff role and context. Results showed that limited differences emerged for staff roles, while more differences were found when exploring the context factor. Overall, the results of this study claim for further attention on the management and design of the sound environment in these facilities.